2002
DOI: 10.1046/j.1469-0705.2002.00742.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of fetal weight by ultrasound: the contribution of additional examiners

Abstract: Measurements by multiple examiners changes only slightly the average number of discrepancies between estimated and actual fetal weights. However, the reduction in major (> 10%) discrepancies is statistically and clinically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
20
1
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 10 publications
4
20
1
3
Order By: Relevance
“…Very few previous studies have dealt with the influence of interexaminer variability on fetal weight estimation. The interexaminer variability observed in this study (about 4%) was similar to that observed by Chang et al [20] and Gull et al [21] . However, in previous studies, interexaminer variability was only estimated using a single equation.…”
Section: Discussionsupporting
confidence: 77%
“…Very few previous studies have dealt with the influence of interexaminer variability on fetal weight estimation. The interexaminer variability observed in this study (about 4%) was similar to that observed by Chang et al [20] and Gull et al [21] . However, in previous studies, interexaminer variability was only estimated using a single equation.…”
Section: Discussionsupporting
confidence: 77%
“…Several studies suggested that multiple measurements by multiple examiners and averaging the results decrease the random error. This was confirmed by the only study included in our review that applied measurement averaging to reduce errors due to observer differences [29]. …”
Section: Discussionmentioning
confidence: 65%
“…There was only one study that investigated the effect of averaging results on FWE [29]. The authors found that especially fetal abdominal circumference (AC) is prone to intra- and interobserver error but can be reduced by averaging results.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gull et al [7] found that multiple ultrasound examiners reduce the proportion of major discrepancies ( 1 10% of the actual birth weight). However, we found that multiple examiners of different working experience only slightly improve the error rate (in a nonsignificant fashion), and that there is no significant change in the proportion of major discrepancies.…”
Section: Discussionmentioning
confidence: 99%